Axon morphology of rapid Golgi-stained pyramidal neurons in the prefrontal cortex in schizophrenia - Banovac, Ivan; Sedmak, Dora; Rojnić Kuzman, Martina; Hladnik, Ana; Petanjek, Zdravko (Croatian medical journal, 2020)
Aim To analyze axon morphology on rapid Golgi impregnated pyramidal neurons in the dorsolateral prefrontal cortex in schizophrenia. Methods Postmortem brain tissue from five subjects diagnosed with schizophrenia and five control subjects without neuropathological findings was processed with the rapid Golgi method. Layer III and layer V pyramidal neurons from Brodmann area 9 were chosen in each brain for reconstruction with Neurolucida software. The axons and cell bodies of 136 neurons from subjects with schizophrenia and of 165 neurons from control subjects were traced. The data obtained by quantitative analysis were compared between the schizophrenia and control group with the t test. Results Axon impregnation length was consistently greater in the schizophrenia group. The axon main trunk length was significantly greater in the schizophrenia than in the control group (93.7 [+ or -] 36.6 [micro]m vs 49.8 [+ or -] 9.9 [micro]m, P=0.032). Furthermore, in the schizophrenia group more axons had visibly stained collaterals (14.7% vs 5.5%). Conclusion Axon rapid Golgi impregnation stops at the beginning of the myelin sheath. The increased axonal staining in the schizophrenia group could, therefore, be explained by reduced axon myelination. Such a decrease in axon myelination is in line with both the disconnection hypothesis and the two-hit model of schizophrenia as a neurodevelopmental disease. Our results support that the cortical circuitry disorganization in schizophrenia might be caused by functional alterations of two major classes of principal neurons due to altered oligodendrocyte development.